Penerapan Pasal 20 Ayat 1 Undang-Undang Nomor 25 Tahun 2009 Tentang Pelayanan Publik Terhadap Standar Pelayanan Pemerintah Terhadap Masyarakat - Utama Syahputra; Seprizal Effendi; Muhammad Jaim Dani (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Public services are a form of state responsibility in fulfilling basic needs and community rights. This research uses normative legal methods by examining Article 20 Paragraph (1) of Law Number 25 of 2009 concerning Public Services. The results show that the low quality of public services is caused by abuse of authority, bribery and nepotism, low apparatus competence, and unprofessional bureaucracy. Internal factors such as weak work systems, lack of performance indicators, and inadequate working conditions also worsen the quality of services provided to the community